2020
DOI: 10.1002/adom.202000273
|View full text |Cite
|
Sign up to set email alerts
|

All‐Perovskite Integrated X‐Ray Detector with Ultrahigh Sensitivity

Abstract: Recently, halide perovskites represent potential materials in X‐ray detection via both direct and indirect ways. Generally, thick active materials are necessary to completely absorb X‐ray photons while inefficient carrier collection leads to low device sensitivity. Besides, though perovskite nanocrystal (NC) scintillators can be used with silicon detectors, they suffer from strong reabsorption problem and the responsivity of silicon detectors is usually low. Herein, an effective strategy based on all‐perovskit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 35 publications
1
68
0
Order By: Relevance
“…The small redshift compared to the PL peak is in accord with other halides. 19,40 It is worth noting Mn 2+ PL is still weak in low doping concentration as shown in Fig. S8, but the RL intensity of Mn3% is much higher than that of pure Cs 3 Cu 2 I 5 .…”
Section: Main Textmentioning
confidence: 93%
See 1 more Smart Citation
“…The small redshift compared to the PL peak is in accord with other halides. 19,40 It is worth noting Mn 2+ PL is still weak in low doping concentration as shown in Fig. S8, but the RL intensity of Mn3% is much higher than that of pure Cs 3 Cu 2 I 5 .…”
Section: Main Textmentioning
confidence: 93%
“…Also, it is reported that taking full advantage of the direct and indirect conversion approaches can achieve better device performance. 4,40 Therefore, we should make a balance between scintillator lm thickness and X-ray absorption. With the increase of scintillator lm thickness, the output power showed a rst rising and then decline trend.…”
Section: Characterization Of Nuclear Batterymentioning
confidence: 99%
“…In recent years, perovskite materials with excellent photoelectric properties have been proved to be potential scintillator materials. [ 124–128 ] In this chapter, we review perovskite and their applications in detectors and imaging from single crystals (SCs), 2D and nanocrystals (NCs)/quantum dots (QDs), and their characteristics are listed in Table 2 .…”
Section: Scintillator Materialsmentioning
confidence: 99%
“…To overcome this difficulty, Li et al. proposed a full perovskite high sensitivity integrated X‐ray detector through carrier management (as shown in Figure a), [ 125 ] which greatly improved the sensitivity of the X‐rays detector. They found that the efficient ultrafast exciton routing in CsPbBr 3 NCs resulted in larger stokes shift, which greatly enhance the quantum yield of PL (>50%) and luminescence efficiency (>threefold).…”
Section: Scintillator Materialsmentioning
confidence: 99%
See 1 more Smart Citation